Gender discrimination in rural non-farm employment in India - Pulla Rao, D. (South Asian Journal of Socio-Political Studies)
The position of women in the society is an index of its civilization. Women as human resource in India constitute about 50 per cent of the total population and about 77 per cent of them live in rural areas. The contribution of female labour force participation will reduce rural poverty. In fact the rural poor have no choice except to raise their work participation either through the use of child labour or the employment of female for earning additional income to meet the household requirements. The percentage of female workforce in agriculture is declining. While that of manufacturing and services sectors is increasing. The share of non-farm female workers was 13.05 per cent in 1961 and it has declined to 10.88 per cent in 1991 then it increased and stood at 25.25 per cent in 2011. Between 1991 and 2011, the increase in share of females has been 9.3 percentage points. The work participation rate is higher in rural areas than in urban areas. The work participation rate for rural females was only 30.98 per cent against 52.36 per cent of rural male work participation in 2011. A considerable variation has been found across the states and activities. A large number of female workers seem to take up jobs in rural non-farm sector in the occupational diversification process. The employment opportunities of females are growing in manufacturing, followed by services and construction, where as they are declining in trade in recent years. In terms of Clark-Kuznets thesis that India is on the path of economic development because the increase in the proportion of occupational structure of workforce from the primary sector to secondary and tertiary sectors had started moving steadily since the 1990s.- Reproduced